El Goliat apócrifo de Tom Gauld: Reinterpretación gráfica de un relato bíblico = Abweichender Titel: The Apocryphal Goliath by Tom Gauld : A Graphic Reinterpretation of a Biblical Story - Guevara Llaguno, M. Junkal (Cauriensia, 2025)
Religion, with all its imagery, stories and figures, is a frequent and multidimensional presence in popular culture, or mass culture. This is evident in the reinterpretations of its stories and characters that can be seen in advertising, television series and graphic designs. One of the most widespread forms of popular expression in recent years is the graphic novel, which has earned the title of "ninth art". These graphic novels are filled with stories of biblical heroes who are easily recognisable in popular culture. Tom Gauld, a British illustrator well known for his comic strips in The Guardian, entered this new genre with a graphic reinterpretation of the story of the battle between David and Goliath. Drawing on E. Panofsky's methodology, this article reflects on the dialogue between philosophy, theology and art, examining Gauld's treatment of the story from iconographic and exegetical points of view. It attempts to reveal how the dialogue between art and faith enriches our understanding of the biblical story.